Network effects on crowdfunding platforms: Exploring the implications of relaxing input control. (16th April 2018) - Thies, Ferdinand; Wessel, Michael; Benlian, Alexander
Abstract: Crowdfunding has emerged as a viable alternative to venture capital or angel investments in order to raise funds for entrepreneurial initiatives. Despite its growing importance, we still know little about the underlying network effects that drive the evolution and growth of crowdfunding platforms. Specifically, is the evolution and growth primarily driven by a growing number of entrepreneurial projects attracting funders, or do funders primarily attract entrepreneurs, or does a reciprocal relationship exist between the two market sides? We also explore whether and how input control, a common gatekeeping mechanism on platforms, has an impact on the formation of network effects. By analyzing eight years of data on the evolution of Kickstarter, one of the leading reward‐based crowdfunding platforms, we find that network effects are asymmetric. An increasing number of entrepreneurial projects has a strong and significant effect on the installed base of funders (cross‐side network effects) and also attracts other entrepreneurs to the platform (same‐side network effects). However, an increased installed base of funders does not have an effect on the growth of either side of the market. We also find that, under weaker input control, cross‐side network effects and same‐side network effects are weaker and less sustainable. Taken together, our exploratory evidence suggests that the relationship between the market sides on crowdfunding platforms might be less reciprocal than expected, having profound implications for entrepreneurs and providers of crowdfunding platforms.